Highly Sensitive and Wearable Liquid Metal‐Based Pressure Sensor for Health Monitoring Applications: Integration of a 3D‐Printed Microbump Array with the Microchannel. Issue 22 (9th October 2019) - Kim, Kyuyoung; Choi, Jungrak; Jeong, Yongrok; Cho, Incheol; Kim, Minseong; Kim, Seunghwan; Oh, Yongsuk; Park, Inkyu
Abstract: Wearable pressure sensors capable of sensitive, precise, and continuous measurement of physiological and physical signals have great potential for the monitoring of health status and the early diagnosis of diseases. This work introduces a 3D‐printed rigid microbump‐integrated liquid metal‐based soft pressure sensor (3D‐BLiPS) for wearable and health‐monitoring applications. Using a 3D‐printed master mold based on multimaterial fused deposition modeling, the fabrication of a liquid metal microchannel and the integration of a rigid microbump array above the microchannel are achieved in a one‐step, direct process. The microbump array enhances the sensitivity of the pressure sensor (0.158 kPa −1 ) by locally concentrating the deformation of the microchannel with negligible hysteresis and a stable signal response under cyclic loading. The 3D‐BLiPS also demonstrates excellent robustness to 10 000 cycles of multidirectional stretching/bending, changes in temperature, and immersion in water. Finally, these characteristics are suitable for a wide range of applications in health monitoring systems, including a wristband for the continuous monitoring of the epidermal pulse rate for cuffless blood pressure estimation and a wireless wearable device for the monitoring of body pressure using a multiple pressure sensor array for the prevention of pressure ulcers. Abstract : In this research, a highly sensitive soft pressure sensor is developed for wearable health monitoring applications. By the integration of 3D‐printed rigid microbumps with liquid metal microchannel, high pressure sensitivity (0.158 kPa −1 @50 kPa) with stable and robust long‐term response is achieved. Continuous pulse monitoring for blood pressure estimation and body pressure monitoring for pressure sore prevention are demonstrated.